PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BANGKIT MAJU BERSAMA, TANGERANG - Muhammad Musyfiq Salami (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The purpose of this study was to determine the effect of motivation and work discipline on the work productivity of employees at PT. Bangkit Maju Bersama either partially or simultaneously. The method used is the associative method. The technique used is random sampling using a sample of 50 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The result of this study is that motivation has a significant effect on work productivity with a coefficient of determination of 0.514. Work discipline has a significant effect on work productivity with a coefficient of determination of 0.426. Motivation and work discipline simultaneously have a significant effect on work productivity with a coefficient of determination of 0.620. This finding confirms that the increase in work productivity is caused by factors of motivation and work discipline of employees, with an opportunity value of 62%. This implies the importance of paying attention to the spirit aspect in carrying out work, and paying attention to the level of work compliance.